Laser spot measurement using simple devices - Bonnett Del Alamo, M.; Soncco, C.; Helaconde, R.; Bazo Alba, J.L.; Gago, A.M. (American Institute of Physics, 2021)
We have designed and tested an automated simple setup for measuring the profile and spot size of a Gaussian laser beam, which exhibits a similar performance to ready-made optical devices, using three light sensors. We use a light dependent resistor as a novel instrument in this approach with good accuracy. We provide the setup in detail in order to be reproduced with the current technology at a standard laboratory. Two profiling techniques were implemented: the imaging technique for the CMOS 2D array (webcam) and scanning knife-edge-like technique using a single photodiode and a light dependent resistor. We apply up-to-date devices, such as a Raspberry Pi, for automation. The methods and sensors were compared to determine their accuracy using lasers of two different wavelengths and technologies. We verify that it is possible to use a webcam to determine the profile of a laser with 1% uncertainty on the beam waist, 1.5% error on the waistline position, and less than 3% error in determining the minimum spot radius. We show that it is possible to use a light dependent resistor to estimate the laser spot size with an 11% error. The photodiode measurement is the most stable since it is not affected by the change in laser intensity.
Keywords: Photodiode; Laser; Optics; Wavelength; Detector; Waistline; Computer science; CMOS sensor; Image sensor; Materials science; Physics; https://purl.org/pe-repo/ocde/ford#1.03.06